Study on Fresh and Hardened Characteristics of Polymer Impregnated No-Fines Concrete - Sameh Yehia, Mayadah W. Falah (International Journal of Advanced Science and Technology, 2020)
In the recent years, the demands on new generation of modern concrete as a results of the industry revolution become important matter. One of these concrete is polymer impregnated no-fines concrete. The scope of this study is to study the fresh and hardened characteristics of selected concrete. The experimental work was done by producing eighteen samples prepared by three different mixing proportions (the samples mainly consists of cement, water and polyester) as a fix proportions but coarse aggregate weight as a variable parameter to obtain the optimal percentage. The failure mechanism was observed and classified, in addition to the density of concrete and voids percentage were taken into consideration. The results show that, the increasing of coarse aggregate weight within the no-fines mixture lead to increase the density along with increasing the compressive, indirect tensile and flexural strength for the samples.